Capstone Project Data Analyst: Analisis Data Untuk Meningkatkan Pengunjung Resort Hotel Di Negara Portugal - Intan Pratiwi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The aim of the results of implementing the data analyst capstone project in increasing visitors to Resort Hotels is to analyze the factors causing the decline in the number of visitors to Resort Hotels. The implementation of the data analyst capstone project to increase visitors at the Resort Hotel includes: identifying the main reasons for the decline in visitors, lack of general attraction or effective promotions, fluctuations in visitors every quarter, and imbalance between various visitor segments. Based on the results of the analysis, recommendations are provided to increase the number of visitors, such as re-evaluating the attractiveness of tourist destinations, adapting facilities and services to visitor needs, collaborating with other local businesses or events, and implementing membership or reward programs. Research methods include understanding business and data, data collection, data cleaning, exploratory data analysis, data visualization and making recommendations based on analysis results. It is hoped that the results of this implementation can help Resort Hotel managers in developing strategies to increase the number of visitors.